2008
DOI: 10.1074/jbc.m707157200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Elastolytic Substrate Specificity in Rodent α-Chymases

Abstract: Divergence of substrate specificity within the context of a common structural framework represents an important mechanism by which new enzyme activity naturally evolves. We present enzymological and x-ray structural data for hamster chymase-2 (HAM2) that provides a detailed explanation for the unusual hydrolytic specificity of this rodent ␣-chymase. In enzymatic characterization, hamster chymase-1 (HAM1) showed typical chymase proteolytic activity. In contrast, HAM2 exhibited atypical substrate specificity, cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…Residues with side chains of intermediate size, such as Val 216 in murine and hamster ␣-chymases and Ser 216 in granzyme M, are associated with elastase and Met-ase activity, respectively, but have little if any ability to hydrolyze peptides after aromatic amino acids. The "gatekeeping" role of residue 216 also is supported by the structural and modeling studies (19,20,23,31), including those in the present work, which suggests that the 216 side chain influences the volume, shape, and hydrophobicity of the binding pocket accommodating the P1 residue of the substrate (see Fig. 6).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Residues with side chains of intermediate size, such as Val 216 in murine and hamster ␣-chymases and Ser 216 in granzyme M, are associated with elastase and Met-ase activity, respectively, but have little if any ability to hydrolyze peptides after aromatic amino acids. The "gatekeeping" role of residue 216 also is supported by the structural and modeling studies (19,20,23,31), including those in the present work, which suggests that the 216 side chain influences the volume, shape, and hydrophobicity of the binding pocket accommodating the P1 residue of the substrate (see Fig. 6).…”
Section: Discussionsupporting
confidence: 58%
“…In the case of elastolytic chymases, notably the mouse chymase MCP-5 and its rat ortholog, the switch from chymotryptic to elastolytic specificity is attributable to natural mutation of a single amino acid (19,20). Similar elastolytic properties have recently been described for hamster ␣ chymase (23). Thus, small changes in structure, including alteration of just one amino acid in the vicinity of the substrate-binding site, can cause large changes in function.…”
mentioning
confidence: 65%
“…Subsequent mutations led to acquisition of specialized activity and higher catalytic efficiency. More generally, these results reveal how small changes in structure in this family of immune peptidases can cause large changes in function, as also occurred in mouse, rat and hamster α-chymase (56, 57), which switched from chymotryptic to elastolytic activity, and in guinea pig α-chymase, which switched from chymotryptic to leu-ase activity (45). Although cathepsin G appears to be microbicidal in mice (6), in the context of chronic airway infection in humans with cystic fibrosis cathepsin G interferes with killing of certain bacteria (11).…”
Section: Discussionmentioning
confidence: 64%
“…The hamster has 2 known chymases. Hamster chymase-1, which converts Ang I to Ang II (35), is a homolog of MMCP4 (27), and hamster chymase-2, which does not, is a homolog of MMCP5 (36). We tested and found that 4-[1-(naphthalen-1-yl methyl)-1H-benzimidazol-2-yl sulfanyl]-butyric acid (CI-B) inhibits purified hamster chymase-1 with a K I of 30.6 ± 3.75 nM (n = 4).…”
Section: Chronic Ace Inhibition Causes Chymase Release Into the LV Ismentioning
confidence: 99%